Legal Protection for Banks as Warehouse Receipt Holders of Bankrupt Agricultural Products - Arizal Pratama, Mohammad; Triyanto, Toni (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This research is entitled